EFEKTIVITAS PROGRAM BARUGA MOICO DALAM MENINGKATKAN KUALITAS RUMAH LAYAK HUNI MASYARAKAT MISKIN DI KECAMATAN RUMBIA TENGAH KABUPATEN BOMBANA - Khadija, Nur; Tuwu, Darmin; Tunda, Amin (Universitas Halu Oleo, 2023)
The study aimed to assess the efficacy of the recently introduced Moico program in enhancing the living conditions of impoverished households in the Rumbia Central Bombana District, as well as examining the advantages gained post-program implementation. A qualitative approach was employed for this investigation. The outcomes of the Baruga Moico program in the Rumbia Central Bombana District revealed both effective and ineffective indicators. Effective aspects included: 1) Accurate targeting, as the Bombana regency government provided assistance in accordance with predefined criteria, focusing on impoverished individuals with inhabitable homes. 2) Attainment of the program's objectives, evidenced by the improved quality of habitable houses for the recipient community. 3) Successful program socialization, ensuring the understanding of the program's processes within the recipient community. Conversely, ineffective implementation was observed in the monitoring of the program, indicating a deficiency in government oversight. The success of the Baruga Moico program contributed to a heightened sense of security and comfort, alleviated the community's household burdens, enhanced confidence within the social environment, met the criteria for suitable housing, and elevated overall welfare through the provision of decent homes.